KORELASI STRUKTUR POPULASI Rhizophora apiculata dan KELIMPAHAN Geloina erosa di HUTAN MANGROVE ACEH BARAT SELATAN - Wintah Wintah; Kiswanto Kiswanto; Maiza Duana (Journal of Aceh Aquatic Sciences, 2017)
The mangroves of the coastal are of West South Aceh have included the restored vegetation of the Post-2004 earth quake and tsunami. This coastal forest was 10 ha wide and extended about 1,5 km from the coastline. Mangrove as the habitat plays a major role in the densiy and distribution of associated organism including Geloina erosa.We reported our study on the locally-named “Totok” shellfish (G. erosa) associated with mangroves in this area. The aim of this research was to determine the correlation between mangrove density with the density of the in habited G. erosa. This research was a survey with a random sampling technique applied to get the data of both the density mangrove and the density of the G. erosa. The relationship of those two was analyzed using software SPSS v19. We found the mangroves of South West Aceh composed of a single species of Rhizophora apiculata. We found the highest density of mangrove was on the station I (7.083 ind./ha) and the lowest density wason the station V (1.033 ind/ha). We found the highest density of G. erosa was on the station I (10.75 ind/m2) and the lowest density is on the station V (1.66 ind/m2). We also found the distribution pattern of G. erosa were grouping caused by the space competition and food provision as a limiting factor. We found the correlation between the density of mangrove with the density of G. erosa were strongly correlated.